Analysis of Image Quality Values of Signal-to-Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR) in T1 and T2 MRI Sequences of Brain Tumors - Pratiwi Sri Wardani; Adrianus Inu Natalisanto; Ainus Sarlianto Sarli (Universitas Negeri Surabaya, 2025)
Brain tumors are considered one of the most serious diseases that require accurate diagnosis to determine appropriate treatment strategies. Magnetic Resonance Imaging (MRI) serves as the primary imaging modality, as it provides detailed visualization of brain structures without the use of ionizing radiation. The quality of MRI images can be evaluated using the parameters of Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR), both of which play an essential role in improving diagnostic accuracy. This study aims to determine and compare the SNR and CNR values of brain tumor MRI images in T1- and T2-weighted sequences, as well as to evaluate image quality based on these parameters. MRI data were obtained from publicly available online databases, followed by Region of Interest (ROI) analysis on tumor areas, healthy tissues (including white matter and gray matter), and background. SNR values were calculated as the ratio of the mean signal intensity of an ROI to the standard deviation of noise, while CNR values were calculated as the difference between the mean signal intensities of two ROIs divided by the standard deviation of noise. The Independent T-Test and Mann-Whitney U test were applied to assess differences between the T1- and T2-weighted sequences. The results demonstrated that the mean SNR and CNR values in the T2-weighted sequence were higher compared to those in the T1-weighted sequence, with statistically significant differences (p < 0.05). These findings indicate that the T2-weighted sequence has a greater ability to differentiate tissues and provide detailed structural visualization. Therefore, the T2-weighted sequence can be recommended as the primary choice for detailed anatomical evaluation and lesion detection in brain tumor MRI examinations.